Role of enterocyte Enpp2 and autotaxin in regulating lipopolysaccharide levels, systemic inflammation, and atherosclerosis - Arnab Chattopadhyay; Pallavi Mukherjee; Dawoud Sulaiman; Huan Wang; Victor Girjalva; Nasrin Dorreh; Jonathan P. Jacobs; Samuel Delk; Wouter H. Moolenaar; Mohamad Navab; Srinivasa T. Reddy; Alan M. Fogelman (Journal of Lipid Research, 2023)
Conversion of lysophosphatidylcholine to lysophosphatidic acid (LPA) by autotaxin, a secreted phospholipase D, is a major pathway for producing LPA. We previously reported that feeding Ldlr−/− mice standard mouse chow supplemented with unsaturated LPA or lysophosphatidylcholine qualitatively mimicked the dyslipidemia and atherosclerosis induced by feeding a Western diet (WD). Here, we report that adding unsaturated LPA to standard mouse chow also increased the content of reactive oxygen species and oxidized phospholipids (OxPLs) in jejunum mucus. To determine the role of intestinal autotaxin, enterocyte-specific Ldlr−/−/Enpp2 KO (intestinal KO) mice were generated. In control mice, the WD increased enterocyte Enpp2 expression and raised autotaxin levels. Ex vivo, addition of OxPL to jejunum from Ldlr−/− mice on a chow diet induced expression of Enpp2. In control mice, the WD raised OxPL levels in jejunum mucus and decreased gene expression in enterocytes for a number of peptides and proteins that affect antimicrobial activity. On the WD, the control mice developed elevated levels of lipopolysaccharide in jejunum mucus and plasma, with increased dyslipidemia and increased atherosclerosis. All these changes were reduced in the intestinal KO mice. We conclude that the WD increases the formation of intestinal OxPL, which i) induce enterocyte Enpp2 and autotaxin resulting in higher enterocyte LPA levels; that ii) contribute to the formation of reactive oxygen species that help to maintain the high OxPL levels; iii) decrease intestinal antimicrobial activity; and iv) raise plasma lipopolysaccharide levels that promote systemic inflammation and enhance atherosclerosis.